Three-Dimensional Reconstruction, by TEM Tomography, of the Ultrastructural Modifications Occurring in Cucumis sativus L. Mitochondria under Fe Deficiency. - Gianpiero Vigani; Franco Faoro; Anna Maria Ferretti; Francesca Cantele; Dario Maffi; Marcello Marelli; Mauro Maver; Irene Murgia; Graziano Zocchi (PLoS ONE, 2015)
Background Mitochondria, as recently suggested, might be involved in iron sensing and signalling pathways in plant cells. For a better understanding of the role of these organelles in mediating the Fe deficiency responses in plant cells, it is crucial to provide a full overview of their modifications occurring under Fe-limited conditions. The aim of this work is to characterize the ultrastructural as well as the biochemical changes occurring in leaf mitochondria of cucumber (Cucumis sativus L.) plants grown under Fe deficiency. Methodology/results Mitochondrial ultrastructure was investigated by transmission electron microscopy (TEM) and electron tomography techniques, which allowed a three-dimensional (3D) reconstruction of cellular structures. These analyses reveal that mitochondria isolated from cucumber leaves appear in the cristae junction model conformation and that Fe deficiency strongly alters both the number and the volume of cristae. The ultrastructural changes observed in mitochondria isolated from Fe-deficient leaves reflect a metabolic status characterized by a respiratory chain operating at a lower rate (orthodox-like conformation) with respect to mitochondria from control leaves. Conclusions To our knowledge, this is the first report showing a 3D reconstruction of plant mitochondria. Furthermore, these results suggest that a detailed characterization of the link between changes in the ultrastructure and functionality of mitochondria during different nutritional conditions, can provide a successful approach to understand the role of these organelles in the plant response to Fe deficiency.